Towards Linking Four Emerging Paradigms in Economic Theory—Regulationist, Institutionalist, Post-modernist, and Post-development (The Pakistan Development Review, 1995)
This paper is an epistemological attempt to synthesise four emerging paradigms in economic theory. These paradigms are the regulationist, the institutionalist, the post-modernist, and the post-development. Arguably, these are paradigms rather than models of behaviour because they each presents an analytical framework for examining different economic phenomena. We shall attempt to show that the four paradigms are useful, complementary, and can be symbiotically linked into a broader paradigm especially to examine the phenomenon of low growth in the region. If we use a modified Kuhnian (1970) model for paradigmatic shifts in a discipline, we can argue that there are three dominating, competing, normal paradigms in economic theory: neoclassical, Marxist, and development theory. In Kuhnian fashion, these three dominant paradigms are pressured by several crises of inability to explain phenomena. Many of these explanational crises are about Less Industrialised Countries (LICs), but increasingly these crises are also about the inability to explain change in the Industrialised Countries (ICs) and the Newly Industrialising Countries (NICs). One, these three paradigms have to explain the differential growth rates of economies. They have to explain the low growth of LICs relative to both the old NICs (Japan, South Korea, Taiwan, Singapore, and Hong Kong) and the new NICs (Malaysia, Indonesia, Thailand, and China). The collapse of the Soviet model also has to be explained. Two, these paradigms have to explain the coexistence of significant levels of poverty with affluence in the LIs, and NICs, and now emergent poverty in the ICs. Three, these paradigms also increasingly have to explain why in a country growth and distribution is biased in favour of particular ethnic and social groups, excluding others, fuelling ethnic and social conflicts within countries and across countries globally. Four, these paradigms have to establish whether the IC market-determined patterns of consumption demand can be satisfied globally